Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcimb.2021.801376
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Fecal Microbiota Transplantation Relieves Gastrointestinal and Autism Symptoms by Improving the Gut Microbiota in an Open-Label Study

Abstract: In the original article, there was a mistake in Figure 1 as published. The dose of oral route FMT was mislabeled. The corrected Figure 1 appears below.The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The results of meta-analysis are reported in the Appendix. (31)]. The study recruitment periods were not reported for these two studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of meta-analysis are reported in the Appendix. (31)]. The study recruitment periods were not reported for these two studies.…”
Section: Resultsmentioning
confidence: 99%
“…The participants were recruited from general hospitals in two major cities, Phoenix, Arizona, and Chongqing, People's Republic of China. All patients completed the entire course of the experiment without withdrawals (30,31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the efficacy of FMT has been observed in changing not only the gut microbiome composition but also the host metabolome and epigenome of immune cells ( 14 ). Several case reports and animal models have also revealed the probable therapeutic effects of FMT in patients with severe multiple sclerosis ( 15 ), autism ( 16 ), multidrug-resistant (MDR) infections ( 17 ), and multiple organ dysfunction in critical patients ( 18 ). Furthermore, the studies also demonstrated the positive effects of immunotherapy on melanoma with FMT in an animal model and clinical trial ( 19 , 20 ).…”
Section: Fmt For Extraintestinal Disordersmentioning
confidence: 99%